The Effectiveness of Making Short Film for Studentsâ€™ Speaking Ability - Affan Andy Wijaya (Tell : Teaching of English Language and Literature Journal, 2016)
As far as the researcherâ€™s knowledge, the research of â€œThe Effectiveness of Making Short Film for Studentsâ€™ Speaking Abilityâ€ is still difficult to find, the researcher formulates the statement of the research, Making Short film is effective for studentsâ€™ speaking ability and the objective of research is to find out whether making short film can effective for studentsâ€™ speaking ability. This research uses experimental design and quantitative method, it is suitable with this research. The subjects are eighth graders ofÂ  VIIIA as control class and VIIIc as experimental class at SMP Muhammadiyah 4 Gadung Surabaya. The data collection uses test, post-test only design as intrument to count the compaired score of the difference classes. The result of post test score is counted using SPSS 1.6 Software to know the significant different between control and experimental class. Based onÂ  the last counted, the researcher count T-test to know the effectiveness of making short film for studentsâ€™ speaking ability and Eta-square to know the effect size of T-test result. T-test result was shown significance between those classes from Equality of variances test is 0.000,Â  whereas P-value is more than 0,05 or P-value > Î± (0.05), so H0 is pushed away. So, the ability of those classes is difference. The result of Eta-square was shown 0.40 which is higher than 0.14. It means the result is very high because 0.40 was exceed the aspect scale 0.14 is large effect. After counted done, making short film proven effective for studentsâ€™ speaking ability.